PENGARUH PENJAMINAN SIMPANAN, CAR, DAN NPL PADA TINGKAT DEPOSIT, RISIKO MORAL HAZARD, DAN NIM - Rofikoh Rokhim; Nevya Wulandary (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
Banking industry plays a very important role in Indonesian economy. Therefore, stability of banking system is considered substantial by the government. Bank Indonesia (BI), the central bank; Indonesia Deposit Insurance Corporation (LPS) and Financial Services Authority (FSA) seeks to preserve the stability of banking system using policy of capital adequacy ratio (CAR), the maximum limit of non-performing loan (NPL) and the obligations to become member of deposit insurance. This study wants to examine whether these regulations affect the level of deposits, moral hazard risk and the net interest margin (NIM) in Indonesian commercial banks in the period 2000-2012. Using a sample of 99 commercial banks with panel data regression method, the result demonstrate implementation of deposit insurance negatively but not significantly affect level of commercial bank deposits while variable CAR and NPL is giving negative and significant effect. Implementation of deposit insurance proved increasing moral hazard risk while variable CAR and NPL have negative and significant effect on the moral hazard risk. Other findings showed implementation of deposit insurance and CAR positively but insignificant affect NIM, but negatively and significant influenced by NPL.